Estimation of efficacy of a home monitoring and communication platform to prevent frailty among older adults in Sweden- a pilot study with a randomized controlled trial design - Marina Taloyan; Maksims Kornevs; Linda Timm; Hassan Alinaghizadeh; Minna Teriö; Sanna Bjälevik-Chronan; Sebastiaan Meijer; Susanne Guidetti (Archives of Gerontology and Geriatrics Plus)
Background: The aging population of the world is increasing. Aging leads to risks for frailty and other chronic diseases and health systems must focus more on prevention to guarantee healthy aging. The primary objective was to estimate the efficacy of the POSITIVE-(The Maintaining and imPrOving the intrinSIc capaciTy Involving Primary Care and caregiVErs) system in improving frailty during a 6-month follow-up period. Method: A randomized controlled, assessor-blinded pilot study (RCT) with 50 individual < 70 years, pre-frail or frail was recruited from a primary care center in Stockholm Region. All participants received a drug review, nutritional recommendations, and a Vivifrail physical exercise program. In addition, the intervention group received POSITIVE including a tablet, an application, and portable measurement devices. The intervention group was monitored remotely by a primary care nurse at the primary health care centre during a six-month follow-up period. Results: At baseline there was a significance between the groups regarding the FTS-5 scale, and significantly more obese participants in the intervention group. The drug reviews showed that three of 43 participants got a review and new diseases were discovered. The test of interactions showed a tendency for significant differences over time between the groups in frailty measured by Fried Frailty Phenotype's and FTS-5 scales. Conclusion: Frailty status over time in the intervention group not differed significantly from the controls. Including individuals to the project even through a pandemic showing that the design is possible for future studies to show effects of new ways of preventing frailty at home. Trial Registration: ClinicalTrials.gov. Registration number: NCT04592146. October 19, 2020. https://clinicaltrials.gov/ct2/show/NCT04592146?term=positive&draw=2&rank=7